Line‐field confocal optical coherence tomography and optical coherence tomography for distinguishing basal cell carcinoma from dermal nevus: A case report - Deborah Winkler; Anna Desch; Martha Paola Mireles; Julia Welzel; Sandra Schuh (Wiley, 2024)
Abstract Basal cell carcinoma (BCC) is the most frequent skin cancer with a rising incidence. It can imitate benign lesions for example, dermal nevus clinically and dermoscopically. Both entities show specific morphologic features in line‐field confocal optical coherence tomography (LC‐OCT) and optical coherence tomography (OCT). The aim was to differentiate both lesions via noninvasive imaging to prevent unnecessary surgery. A 63‐year‐old woman presented with a light brownish nodule on the left cheek and a brownish nodule on the right nasal slope/cheek, which were both evident since a few months. The clinical and dermoscopic appearance of both lesions was very similar including the differential diagnosis of a dermal nevus or BCC. Dynamic OCT of the lesion on the left cheek showed multiple hyporeflective nodules in the dermis with hypervascularization. Using LC‐OCT several hyporeflective round to ovoid nodules with hyporeflective clefting embedded in a hyperreflective surrounding connective tissue could be observed. These specific morphological criteria called millefeuille pattern led to the diagnosis of a nodular BCC. The lesion of the right cheek presented with a thickened epidermis and elongated rete ridges in dynamic OCT. Upon LC‐OCT examination a so‐called large wave like pattern presenting as undulating hyporeflective and hyperreflective lobular structures could be identified. Therefore, the diagnosis of a dermal nevus was made. Both lesions were identified correctly as confirmed histopathologically after shave excision. Since BCC can imitate benign lesions for example, dermal nevi, the use of OCT and LC‐OCT can facilitate the identification of BCC and its imitators. Noninvasive imaging can help to avoid unnecessary biopsy especially in areas where the skin is vulnerable to punch biopsy.